2004
DOI: 10.1001/archpsyc.61.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Disulfiram and Cognitive Behavior Therapy in Cocaine-DependentOutpatients

Abstract: Disulfiram and CBT are effective therapies for general populations of cocaine-dependent individuals. Disulfiram seems to exert a direct effect on cocaine use rather than through reducing concurrent alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
257
3
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 395 publications
(275 citation statements)
references
References 64 publications
(62 reference statements)
7
257
3
8
Order By: Relevance
“…Although preliminary findings indeed supported the efficacy of disulfiram in cocaine/alcohol codependent individuals (Carroll et al, 1998, results from three recent studies strongly suggest that comorbid alcohol use is not necessary for disulfiram treatment of cocaine dependenceFin fact, nonalcohol-dependent subjects may derive even more benefit from disulfiram treatment than those who also abuse alcohol (George et al, 2000;Petrakis et al, 2000;Carroll et al, 2004). Because the drug combination of disulfiram and cocaine in the absence of alcohol does not result in acetaldehyde accumulation, the reduction of cocaine use with disulfiram treatment must depend on an interaction other than inhibition of aldehyde dehydrogenase.…”
Section: Disulfiram and Cocaine Dependencementioning
confidence: 92%
“…Although preliminary findings indeed supported the efficacy of disulfiram in cocaine/alcohol codependent individuals (Carroll et al, 1998, results from three recent studies strongly suggest that comorbid alcohol use is not necessary for disulfiram treatment of cocaine dependenceFin fact, nonalcohol-dependent subjects may derive even more benefit from disulfiram treatment than those who also abuse alcohol (George et al, 2000;Petrakis et al, 2000;Carroll et al, 2004). Because the drug combination of disulfiram and cocaine in the absence of alcohol does not result in acetaldehyde accumulation, the reduction of cocaine use with disulfiram treatment must depend on an interaction other than inhibition of aldehyde dehydrogenase.…”
Section: Disulfiram and Cocaine Dependencementioning
confidence: 92%
“…Adapted from the Time Line Follow-Back interview (Sobell & Sobell, 1992), which has been shown to be a reliable and valid instrument for monitoring substance use (Fals-Stewart, O'Farrell, Freitas, McFarlin, & Rutigliano, 2000), the SUC uses a similar calendar method to allow for a continuous and reliable evaluation of daily substance use (Carroll et al, 2004).…”
Section: Assessment Proceduresmentioning
confidence: 99%
“…However, recent controlled trials of several medications, namely, disulfiram, topiramate, modafinil, and others, suggested that some medications added to counseling may provide an advantage over placebo treatment for cocaine dependence (See respectively : Carroll, Fenton, Ball, Nich et al, 2004;Dackis, Kampman, Lynch, Pettinati et al, 2005;Kampman, Pettinati, Lynch, Dackis et al, 2004). To date, however, disulfiram has had more published articles than any other medication in support for its use in the treatment of cocaine dependence (see Carroll et al, 2004;Carroll, Nich, Ball, McCance et al, 2000;Carroll, Nich, Ball, Mccance et al, 1998;Gossop & Carroll, 2006;Grassi, Cioceb, Dei Giudicib, Antonillia et al, 2007), particularly in men (Nich, McCance-Katzb, Petrakis, Cubellsa et al, 2004;Petrakis, Carroll, Nich, Gordon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%